PERTANGGUNGJAWABAN PENGELOLAAN ANGGARAN DI DEWAN PERWAKILAN RAKYAT KABUPATEN ACEH BARAT. - Nila Trisna, Husni A. Jalil, Eddy Purnama. (Jurnal Ilmu Hukum, 2015)
Abstract:The research shows that the management of budget is done by the Secretary of the House of Representative has not been well managed as demanded by the principles of budget drfating that are efficient, not luxurious, effective, based on the rule. It results from the planning of budget by the Secretariat of the House of Representative of Aceh Barat annually is always done by maximal budget approach hence it is not paying attention on proper principle of properness, inability of regional budget, and the ability of output of the working is not balanced to the budget. The implementation of budget by the Secretariat of the House states that the amount of Regional Spending that is budgeted in DPA of the Secretariat of the House is not the highest level for every spending. Thus, the spending of the Secretariat of the House of Representative has not been conducted based on not glamour, not luxury, effective, efficient and in accordance with the legal principles of the law. The monitoring of budget of the House of representative of Aceh Barat as similar as the spending that it has not been well conducted based on the principles of not glamour, cheap, effective, efficient and in accordance with the rules. The monitoring of budget by the House as ruled in Article 42 verse (1) c of the Act Number 32, 2004 has not provided the explanation regarding the power of monitoring done by the Regional/Municipality House of Representative toward the management of regional budget, including the management of budget at the House of Representative, hence in its implementation the House seems to have the power to do monitoring that has technical characteristic that is a part of the power done by the internal governmental monitor, inspector of budget. Key words: Responsibility, Budget Management, the House of Representatives of Aceh Barat. Abstrak: DPR Kabupaten/Kota mempunyai hak untuk menggunakan anggaran yang ditetapkan dalam APBK dan diadministrasikan oleh Sekretaris DPR Kabupaten/Kota, yang dalam melakukan pengelolaan Anggaran harus berpedoman Peraturan Pemerintah Nomor 21 tahun 2007 Tentang Kedudukan Protokoler dan Keuangan Pimpinan dan Anggota DPRD. Fungsi penganggaran yang dilakukan oleh DPRK Aceh Barat yang meliputi kegiatan perencanaan anggaran, pelaksanaan anggaran dan pengawasan anggaran sering mengabaikan prinsip-prinsip penyusunan anggaran daerah yang baik, yaitu prinsip hemat, tidak mewah, efektif dan efisien. Hal ini dapat terlihat dari besarnya jumlah anggaran yang digunakan oleh DPRK Aceh Barat untuk setiap satu tahun anggaran. Hal ini disebabkan dalam perencanaan anggaran Sekretariat DPRK Aceh Barat setiap tahunnya selalu dilakukan dengan pendekatan anggaran maksimal, sehingga dirasakan kurang memperhatikan asas kepatutan. Pelaksanaan anggaran oleh Sekretariat DPRK Aceh Barat menentukan bahwa jumlah Belanja Daerah yang dianggarkan dalam DPA Sekretariat DPRK Aceh Barat merupakan batas tertinggi untuk setiap pengeluaran belanja. Pengawasan anggaran DPRK Aceh Barat sebagaimana terdapat dalam ketentuan Pasal 42 ayat (1) huruf c Undang-Undang Nomor 32 Tahun 2004 tidak memberi penjelasan yang cukup jelas tentang kewenangan pengawasan yang dilakukan oleh anggota DPRK terhadap pengelolaan anggaran daerah, sehingga dalam implementasinya DPRK mempunyai kewenangan melakukan pengawasan yang bersifat tehnis, sedangkan dalam kenyataannya pengawasan yang bersifat tehnis merupakan kewenangan yang dilakukan oleh aparat pengawas intern pemerintah dalam hal ini adalah oleh Inspektorat. Supaya pengelolaan anggaran dapat berjalan dengan baik maka disarankan agar peraturan perundang-undangan yang berhubungan dengan perencanaan,pelaksanaan dan pengawasan anggaran DPRK dapat dipedomani dengan baik. Kata kunci : Pertanggungjawaban, Pengelolaan Anggaran DPRK Aceh Barat.